Post-War Road Development in India (Second Reprint) Proceedings of the Conference of Chief Engineers of Provinces and States Held at Nagpur from the 15th to 18th December, 1943. - Planning Commission (Planning Commission, 1943)
The Conference of Chief Engineers convened by the Government of India met under the Chairmanship of Mr. J. Vesugar. Consulting Engineer (Roads) to consider ways and means of planning future road development. Thirty delegates (names in Appendix I) representing the Provinces and States of India, the War Transport Department, and the Army, met at 11 a.m. on the 15th December 1943, in the Committee room of the Secretariat at Nagpur.
Ministry of Transport Roads Organization, Government of India